2004
DOI: 10.1002/jmv.20180
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing for detection of in vitro infectivity of plasma pools contaminated with B19 virus

Abstract: B19 virus can be transmitted by contaminated blood or blood products. Recent observations, in healthy volunteers, suggest that active B19 infection can follow the administration of plasma pools with a concentration > or =10(7) genome equivalents/ml (geq/ml) of B19 DNA. However, patients receiving batches with levels of virus DNA lower than 10(4) geq/ml do not show any evidence of transmission of the virus. The aim of the study was to show, by in vitro assays, a threshold of viral load in B19 contaminated plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…As with the IF assay, they also confirmed that the UT7/Epo-S1 cells were the most sensitive cell line, and using these cells, we could detect infectious virus with inoculums of ∼10 4 genome copies. This is also in keeping with other published results that suggest the ratio of infectious virus:genome copies is 1:10,000 (Bonvicini et al, 2004;Miyagawa et al, 1999), not dissimilar to that of other Parvoviridae (Tattersall and Cotmore, 1988).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As with the IF assay, they also confirmed that the UT7/Epo-S1 cells were the most sensitive cell line, and using these cells, we could detect infectious virus with inoculums of ∼10 4 genome copies. This is also in keeping with other published results that suggest the ratio of infectious virus:genome copies is 1:10,000 (Bonvicini et al, 2004;Miyagawa et al, 1999), not dissimilar to that of other Parvoviridae (Tattersall and Cotmore, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, infection and neutralization assays based on UT7/Epo cells (Bostic et al, 1999), KU812Ep6 (Blumel et al, 2002;Bonvicini et al, 2004;Miyagawa et al, 1999;Saito et al, 2003) and UT7/Epo-S1 (Prikhod'ko et al, 2005) cells have all been described. More recently, cells that are not fully permissive for B19 infection have also been evaluated (Caillet-Fauquet et al, 2004) However, there have been no attempts to compare the different cell types or sensitivity of the different methods.…”
Section: Discussionmentioning
confidence: 99%
“…Of additional interest is the observation that the infectivity titers are approximately 4 log lower than the genomic titer determined by short‐amplicon quantitative PCR for the infectious samples (5‐7.7 log/mL vs. 11 log/mL). This is consistent with the observations of others, as well as our previous results, 20,24 , 29‐31 and may be explained by the presence of noninfectious B19 genome fragments and noninfectious mutants 32,33 . These observations highlight the need to carefully evaluate quantification of genomic equivalents based on small‐amplicon detection as a surrogate for infectivity in blood products.…”
Section: Discussionsupporting
confidence: 93%
“…Owing to the global prevalence of B19V Genotype 1, 30 to 60 percent of adults carry antibodies against B19V (B19V immunoglobulin G [IgG]), with a good correlation between antibody prevalence and age 10 . Consequently, the presence of B19V IgG was found in all of the few plasma pools for manufacturing so far investigated 11‐14 . Mostly due to the lack of a widely available B19V infectivity assay, however, no information was available with respect to antibody function, that is, B19V neutralization, and whether this potentially clinically relevant variable would correlate with the presence of B19V antibodies detected by, for example, enzyme‐linked immunosorbent assay (ELISA).…”
mentioning
confidence: 99%